2013
DOI: 10.1038/bjc.2013.679
|View full text |Cite
|
Sign up to set email alerts
|

The effects of multidisciplinary rehabilitation: RePCa—a randomised study among primary prostate cancer patients

Abstract: Background:The objective of this study is the effectiveness of multidisciplinary rehabilitation on treatment-related adverse effects after completed radiotherapy in patients with prostate cancer (PCa).Methods:In a single-centre oncology unit in Odense, Denmark, 161 PCa patients treated with radiotherapy and androgen deprivation therapy were randomly assigned to either a programme of two nursing counselling sessions and two instructive sessions with a physical therapist (n=79) or to usual care (n=82). Primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
7
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 30 publications
0
63
7
7
Order By: Relevance
“…86 demonstrated improvements in variables related to the UI symptom, intensity, frequency, difficulty and limitation of activity after 24 weeks of PFMT (p ≤ 0.0001). These results were further confirmed by Dieperink in an RCT of Danish population ( n  = 161) stratified to multidisciplinary rehabilitation after RT/ADT, where nursing counselling sessions and therapist‐guided instructive sessions resulted in significant improvements of LUTS symptoms vs. standard care 75.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…86 demonstrated improvements in variables related to the UI symptom, intensity, frequency, difficulty and limitation of activity after 24 weeks of PFMT (p ≤ 0.0001). These results were further confirmed by Dieperink in an RCT of Danish population ( n  = 161) stratified to multidisciplinary rehabilitation after RT/ADT, where nursing counselling sessions and therapist‐guided instructive sessions resulted in significant improvements of LUTS symptoms vs. standard care 75.…”
Section: Discussionmentioning
confidence: 62%
“…Two small studies have assessed the effects of PFMT and multidisciplinary rehabilitation after RT/ADT, and both demonstrated significant improvements with PFMT in this patient group 75, 77. Faithfull et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Two papers compared the irradiated subjects to non-cancer, non-irradiated subjects [28,29] and two more to subjects with cancer but who did not receive radiation [36,37], and three others compared to preradiation measures [38][39][40]. Two articles rated "low to moderate quality" [40,29], two rated "good quality" [36,28], and three of "excellent quality" [38,39,37] (Table 2). In a retrospective cohort study by Theisen et al [40], resting and maximal squeeze pressure data measured by anal manometry was reported (Table 4).…”
Section: The Effects Of Rt On Pfm Function Pfm Strengthmentioning
confidence: 99%
“…Consequently, a trend toward a higher proportion of low-strength scores is likely for the subjects who received RT. Dieperink et al [38], in 2013, presented a RCT where pre-RT baseline measures were available. With the collaboration of the authors, additional paired t tests (data available in Table 5) were conducted, and it was acknowledged that when measured digitally using the Oxford scale, maximal PFM contraction, static strength, and dynamic strength were not significantly different pre-to postradiation.…”
Section: The Effects Of Rt On Pfm Function Pfm Strengthmentioning
confidence: 99%